Morphological and chemical features of submarine groundwater discharge zones in the south-eastern part of the Baltic Sea - Krek Alexander V; Danchenkov Alexander; Mikhnevich Galina Sergeevna (Russian Journal of Earth Sciences)
The complex study of the bottom sediments and near-bottom water layer of the Gdansk Deep revealed the Ca maximum anomaly, marking the discharge of the Oxford-Titonian aquifer. The discharge zone is associated with gas-saturated sediments, which is caused by a common pathway of aqueous and gaseous fluids upraise along tectonic faults. The detailed survey of a seabed topography and acoustic survey of the sediments upper layer helped to specify the area of gas-saturated sediments and the size of the pockmarks.